Dynamic response of economic growth to environmental degradation in Nigeria - Olabisi, Olabode Eric; Aderibigbe, Olasimbo; Sadibo, Olanrewaju Victor (Energy Economics Letters, 2025)
With the global climate change threat, achieving environmental sustainability has become a major concern among the world leaders, scholars, and researchers in the fields of environmental and economic growth-related studies. The aim of this paper is to examine the dynamic response of economic growth to environmental degradation in Nigeria from 1980 to 2022. Using the econometric technique of autoregressive distributed lags (ARDL) model, findings show that while environmental degradation often accompanies economic growth, its impact on long-term growth is weak and not statistically significant. Variables such as carbon emissions, financial development, and trade openness show mixed results regarding their influence on economic growth. Interest rates are identified as having a minor positive effect on GDP, particularly in the short run. The study concludes that a growing population positively affects GDP by expanding the labour force and enhancing economic productivity. The study emphasises the need for integrated economic policies that consider both financial and environmental management to ensure sustainable growth.